PENGUKURAN TRANSPARANSI KEUANGAN DAERAH BERBASIS WEBSITE PADA KABUPATEN/KOTA DI INDONESIA - Alwahidi, Muhammad Rizki; Darwanis, Darwanis (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this study was to measure the level of regional financial transparency and see the correlations between the wealth of the local government and BPK's opinion on the level of regional financial transparency in districts / cities in Indonesia. The sample taken in this study is probability sampling with Slovin method. The number of samples used in this study is 224 districts / cities. The data obtained were analyzed using Simple Pearson correlation method. The results of this study indicate that the average level of regional financial transparency in districts / cities in Indonesia is 18.85%. The highest value is 71% obtained by Natuna Regency and the lowest value is 2.09 obtained by 48 regencies / cities in Indonesia. The results of this study also show that the level of local government wealth and BPK's Opinion have a very low relationship to the level of regional financial transparency.